Avaliação do Conselho do Orçamento Participativo de Fortaleza - COP Processo Participativo e Cidadania - Pessoa, Maria Aglais Gadelha (2010)
The objective of the present essay is to investigate the limits and potentialities of the Fortaleza Collaborative Budget City Council (to be called COP – Conselho de Orçamento Participativo) in the development of popular collaboration, taking an ‘ex post facto’ assessment as basis, considering the 2005/2008 quadriennium, which was the first period under the management of the mayor Luiziane Lins. The theoretical references which were used about participation, government and public politics are based on the main up-to-date researchers with the focus on principles of a pedagogical dimension to the political emancipation and an active citizenship. The announced hypothesis is based on the conjecture that the Collaborative Budget is associated to the question of citizenship, as a conquered right, that demands some space to democratic and transparent actions, being able to influence the production of public politics. The research verifies that, in Fortaleza, the COP is innovative as it presents an intern arrangement of power featured in the typology ‘society-government’, where there is civil society domination on the constitution of the council, with potentiality to enhance associations of human life linked to possibilities of a democratic politics active everyday education. Notwithstanding, the research concludes that the COP, as an institutional extension, still presents some limits, most of all, related to two main questions: the weakness of its power to define and deliberate city public politics and the absence of financial resources for attending the demands. In the same sense, the initial hypothesis was disproved, considering that under the governmental actor’s point of view, the COP assembles all the necessary conditions to democratize the city budget.